Archaeology, Gender, and Journalism: Presencia y representación de las mujeres que investigan el pasado en los periódicos españoles en 2022 - Maciá-Barber, Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The media increases the coverage of findings about the past. Preventing discrimination based on sex is a principle of journalistic codes of ethics. From a gender perspective, the study addressed the presence of female scientists as newsworthy subjects and like expert sources. Messages (n=59) in the two main legacy Spanish newspapers (El País, El Mundo) were analysed using quantitative and qualitative techniques. The voice of the professional of archaeology is preponderant and the authorship of specialized reporters prevails. Women are secondary and relegates them as scientists, specialists, and reporters.